2013
DOI: 10.14260/jemds/1188
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Hypotension During Propofol Induction: A Comparison of Preloading With Ringer Lactate and Intravenous Ephedrine

Abstract: ABSTRACT:The induction of general anaesthesia with propofol, however, has been associated with a decrease in systolic arterial blood pressure. Various measures to prevent hypotension include preloading with fluids (colloids and crystalloids) and use of vasopressors including ephedrine, dopamine, dobutamine, and metaraminol. The aim of the present study was to compare the three different regimes for the prevention of hypotension during induction of anaesthesia. MATERIALS AND METHODS: Ninety patients, classified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…18 Agarwal et al also concluded that preoperative administration of ephedrine failed to prevent propofol-induced hypotension, but preoperative volume loading with 10mL/kg of ringer lactate successfully antagonized it. 19 Malla et al conclude that crystalloid preloading is not efficacious in preventing hypotension compared to gelatine and ephedrine which were markedly attenuated, but does not fully abolish the decrease in blood pressure caused by induction. 20 Dhungana et al found that preloading with colloid (Haemaccel, 10 mL/kg intravenously over 10-15 minutes) or prior injection of sympathomimetic ephedrine (0.2 mg/kg iv), prior to induction of anesthesia with propofol (2.5 mg/kg iv) though are not fully efficacious in preventing hypotension caused by propofol induction, both decrease the incidence in a significant number of patients with heart rate less than baseline value in the colloid group.…”
Section: Discussionmentioning
confidence: 99%
“…18 Agarwal et al also concluded that preoperative administration of ephedrine failed to prevent propofol-induced hypotension, but preoperative volume loading with 10mL/kg of ringer lactate successfully antagonized it. 19 Malla et al conclude that crystalloid preloading is not efficacious in preventing hypotension compared to gelatine and ephedrine which were markedly attenuated, but does not fully abolish the decrease in blood pressure caused by induction. 20 Dhungana et al found that preloading with colloid (Haemaccel, 10 mL/kg intravenously over 10-15 minutes) or prior injection of sympathomimetic ephedrine (0.2 mg/kg iv), prior to induction of anesthesia with propofol (2.5 mg/kg iv) though are not fully efficacious in preventing hypotension caused by propofol induction, both decrease the incidence in a significant number of patients with heart rate less than baseline value in the colloid group.…”
Section: Discussionmentioning
confidence: 99%